Structuring electronic discourse for inter-organisational decision making - Sheffield, Jim (School of Management Working Papers, 2013)
Electronic technology is increasingly used to support inter-organisational decision making groups in situations where the objectives of participants are divergent and power diffused. This creates conceptual and practical difficulties for participants and sponsors alike. How should the problem be structured? How should success be measured? What type of model should drive the problem structuring process? While the literature on electronically-supported inter-organisational decision making raises issues such as these it does not provide a solution. The current research draws on the problem structuring literature to fill this gap. A conceptual problem structuring model is developed from the theoretical perspectives of pluralism and communicative action. The model is applied to structure strategically important electronically-supported inter-organisational decision making meetings sponsored by government organisations. The focus question is: ‘Does electronic discourse increase the success of inter-organisational decision making? If so, what problem structuring principles and processes were employed, and what level of participant satisfaction was achieved?’